IMPLEMENTASI KESETARAAN GENDER PADA PENDIDIKAN ANAK USIA DINI DI SEKOLAH - Selia Dwi Kurnia (AN-NISA, 2018)
This article shows the implementation of gender equality in early childhood education in schools. Gender equality in the equality of position between men and women, without any differences with gender. Understanding gender equality in schools can make students not dominate what is their responsibility. Therefore, it is necessary to understand gender equality in schools so that students can explore their skills and abilities to be more qualified.